PENGEMBANGAN MEDIA VIDEO ANIMASI PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR DALAM MENDUKUNG PEMBELAJARAN DARING DI ERA PANDEMI - Jendriadi; Adhya Muqarramah Rahayu; Vivi Puspita; Lisa Yuniarti (LP2M Universitas Adzkia, 2020)
Learning media is a means or tools used by teachers to convey learning messages to assist in the learning and teaching process. One of the media that can be used by the teacher for the learning process is animation video media. Based on the results of field observations conducted by researchers in grade IV SDN 17 Batu Kunit, Pesisir Selatan Regency on February 17, 18, and 19, 2020. Only a few students are interested in taking part in the learning because the media used is not attractive. On the implementation of the 2013 curriculum. Furthermore, based on the results of interviews conducted by researchers on July 20, 2020, several students and class IV teachers of SDN 17 Batu Kunit, Pesisir Selatan Regency. Integrated thematic learning is less attractive to students, so that learning is ineffective and requires a lot of time. This research is a research development or Research and Development model developed by Borg and Gall. The potential and problem stages were conducted by interviewing teachers to determine basic competencies in research. The stage of gathering information was carried out through interviews and field observations. The product design stage involves writing storyboards and scripts, producing video and audio media and preparing supporting components, then the researcher uploads to https://drive.google.com/file/d/14gqmlzKiD7GQcaZjFUAFx0LyXqVHQ235/view?usp=drivesdk.Video eligibility based on the assessment of linguists with a percentage of 88%. The feasibility of the animated video is based on the assessment of 2 material experts with a percentage of 93%. The feasibility of the animated video based on the assessment of media experts with a percentage of 94%. Based on all the ratings from the video animation experts it is in the very decent category. Keywords: Learning Media, Animated Videos, Integrated Thematic Learning